Black/White Differences in Perceived Weight and Attractiveness among Overweight Women - Taona P. Chithambo; Stanley J. Huey (Journal of Obesity)
Numerous studies have reported that Black women are more satisfied with their bodies than White women. The buffering hypothesis suggests that aspects of Black culture protect Black women against media ideals that promote a slender female body type; therefore, Black women are expected to exhibit higher body esteem than White women. To test this hypothesis, the current study aimed to assess the influence of race on weight perception, perceived attractiveness, and the interrelations between body mass index (BMI) and perceived attractiveness among overweight and obese women. Participants were 1,694 respondents of Wave IV of the National Longitudinal Study on Adolescent Health ( years). Black () or White () obese or overweight women were included in the current study. As expected, Black women reported lower perceived weight and higher attractiveness than White women, despite higher body mass for Black women. Furthermore, race moderated the relationship between BMI and perceived attractiveness; for White women, a negative relationship existed between BMI and attractiveness, whereas for Black women, BMI and attractiveness were not related. The study findings provide further support for the buffering hypothesis, indicating that despite higher body mass, overweight Black women are less susceptible to thin body ideals than White women.